2004
DOI: 10.1111/j.1095-8312.2004.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

Are neopolyploids a likely route for a transgene walk to the wild? The Aegilops ovata × Triticum turgidum durum case

Abstract: Spontaneous hybridization between durum wheat ( Triticum turgidum durum ) and Aegilops ovata is regularly observed in nature. The frequency of spontaneous amphiploidy in sympatric populations was estimated at 10 -6 (direct in situ observations and germinated seed collected from A. ovata plants). In nursery conditions some genotype combinations gave frequencies that were much higher at 10 -3 . Genomic in situ hybridization revealed that fertile amphiploids had arisen through unreduced gametes, and that some of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 34 publications
2
30
0
1
Order By: Relevance
“…crassa (2n = 42, DDDDMM), Ae. triuncialis (2n = 28, UUCC), Hynaldia villosa (2n = 14, VV) and rye (Secale cereale L., 2n = 14, RR) as well as in haploid plants of T. t. durum (Blanco et al 1983;Stefani et al 1983;Liu et al 1986;Xu and Dong 1992;Balatero and Darvey 1993;Pignone 1993;Xu and Joppa 2000;Jauhar et al 2000;David et al 2004). Obviously, meiotic restitution usually takes place in a plant with a haploid genome as a result of failure of either the first or the second meiotic division.…”
Section: Introductionmentioning
confidence: 99%
“…crassa (2n = 42, DDDDMM), Ae. triuncialis (2n = 28, UUCC), Hynaldia villosa (2n = 14, VV) and rye (Secale cereale L., 2n = 14, RR) as well as in haploid plants of T. t. durum (Blanco et al 1983;Stefani et al 1983;Liu et al 1986;Xu and Dong 1992;Balatero and Darvey 1993;Pignone 1993;Xu and Joppa 2000;Jauhar et al 2000;David et al 2004). Obviously, meiotic restitution usually takes place in a plant with a haploid genome as a result of failure of either the first or the second meiotic division.…”
Section: Introductionmentioning
confidence: 99%
“…Aegilops hybrids are highly sterile, but descendents can be found after back-crossing to any of the parents or spontaneous amphiploidy. Thus, these hybrid-derived forms are acknowledged as the most likely bridges for wheat gene flow in nature [David et al, 2004].…”
mentioning
confidence: 99%
“…There is clear evidence that viable seeds are produced by functional 2n gametes in durum wheat haploids (Jauhar et al, 2000;Jauhar, 2003). Similarly, David et al (2004) observed that fertile Ae. geniculata × T. turgidum durum hybrids always produced total or partial amphiploids in their offspring.…”
Section: Discussionmentioning
confidence: 97%
“…In the amphiploids every chromosome of the original hybrids is represented twice and each chromosome has a homologous partner to pair at meiosis. Thus, meiosis is regular and fertile derivatives can be obtained from hybrids whose sterility was caused by chromosomal unbalance and irregularity (Bretagnolle and Thompson, 1995;Ramsey and Schemske, 1998;David et al, 2004). In their review on hybridization between wheat and its relatives, Zaharieva and Monneveux (2006) mentioned that Tschermak and Bleier (1926) were the first to obtain an amphiploid species as a result of the spontaneous doubling of the chromosomes of a wheat hybrid produced by the cross of T. turgidum dicoccoides with Ae.…”
mentioning
confidence: 99%
See 1 more Smart Citation